Education Game 'Litter Rush' Care For The Environment From Garbage Android Based - Muhamad Sarwo Edy; Cindy Taurusta (JOINCS (Journal of Informatics, Network, and Computer Science), 2019)
The purpose of this study was to create an educational game for children to dispose of waste. The method used is the Research and Development method using the ADDIE model. The result is a shooter type educational game about collecting interesting rubbish as an educational media and a hobby dealer. The conclusion is that the ADDIE Model is very helpful, in planning the ADDIE model is able to accommodate things conveyed by media experts and material experts so that they can be collaborated with user needs at the evaluation stage. The achievement of 4 aspects including functionality, reliability, compability and playability reached 96.2% in the very feasible category.